Probing the mechanics of aqueous two-phase extraction using large diameter single-walled carbon nanotubes. (30th July 2018) - Turek, Edyta; Wasiak, Tomasz; Stando, Grzegorz; Janas, Dawid
Abstract: We have demonstrated that large diameter (1.8 ± 0.4 nm) carbon nanotubes (CNTs) can be separated by means of the aqueous two-phase extraction (ATPE). This rapid and convenient tool has enabled us to isolate fractions of particular CNT diameter distribution. We have shown how a range of parameters can be used to fine tune the characteristics of the isolated material. Interestingly, by varying the pH of the medium, we have suppressed the extraction of low diameter CNTs and only large diameter CNTs were obtained. A number of other factors such as selected surfactant concentration steps, temperature or amount of starting CNT material have been found to have a significant effect on the end result of the CNT differentiation. The findings have provided us with more insight regarding the underlying mechanics of ATPE for processing polydisperse CNT mixtures.